THE ROLE OF MULTIMEDIA TOOLS IN DEVELOPING STUDENTS’ SPEAKING SKILLS - Raxmatova Maftuna Ma'murjon kizi,; I. Umrzokov, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This research article examines the effectiveness of video-based multimedia tools in developing speaking skills among undergraduate students in Uzbekistan. The study investigates how audiovisual content influences students’ vocabulary acquisition, fluency, grammatical accuracy, and interactional competence. The results of a quasi-experimental study demonstrate that multimedia-assisted learning significantly enhances learners' oral proficiency, offering valuable implications for English language pedagogy at the tertiary level.